Analisis finansial usaha ternak ayam ras petelur (studi kasus CV Muara Puncak di Desa Muara Putih Kecamatan Natar) - Ilyas Wiguna, Ahmad; Eka Wati, Novi; Herdiansyah, Riko (JDP: Jurnal Dunia Peternakan, 2023)
The purpose of this research is to analyze financially and analyze the feasibility of laying hens CV. Puncak Estuary. The research was conducted in October - December 2022. Located in Muara Putih Village, Natar District, South Lampung Regency. The research method used in this study is a case study. The type of data used is descriptive, quantitative and qualitative. The data sources used are primary data and secondary data. Case studies are used with descriptive analysis with a quantitative approach, namely presenting a summary of data or values ​​calculated based on available data or data collected. The results of the research show that the financial analysis is Net Present Value (NPV) > 0, Revenue Cost Ratio (RCR) > 1, Internal Rate of Return (IRR) > cost of capital, Break Event Point (BEP) has been fulfilled, Return On Investment (ROI) ≥ 10%, and Payback Period (PP) < business year that has been run.